Geography and literature: a reflection - Diva Aparecida Machado Olanda (Geosul, 2008)
This article intends to approach Geography and Literature. The main goal is to debate and find out converging features of Geography and Literature in a way that links both fields to allow literature to be a source of geographical investigation. The theorybasis focus on a cultural aproach to Geography. Therefore this discussion runs around culture, value and human subjectivity to understand the relations between human beings and the environment. Here literature is considered as representation of reality. Representation here is seen a process of absorbtion of reality.